2014
DOI: 10.1111/jpi.12157
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents mitochondrial dysfunction and insulin resistance in rat skeletal muscle

Abstract: Melatonin has a number of beneficial metabolic actions and reduced levels of melatonin may contribute to type 2 diabetes. The present study investigated the metabolic pathways involved in the effects of melatonin on mitochondrial function and insulin resistance in rat skeletal muscle. The effect of melatonin was tested both in vitro in isolated rats skeletal muscle cells and in vivo using pinealectomized rats (PNX). Insulin resistance was induced in vitro by treating primary rat skeletal muscle cells with palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 45 publications
6
72
0
2
Order By: Relevance
“…The above hypothesis is supported by the observation that the exposure to saturated fatty acids of isolated mitochondria (Abdul-Ghani et al 2008) or cells (Hirabara et al 2010, Jheng et al 2012, Yang et al 2012, Teodoro et al 2014 clearly elicits mitochondrial dysfunction, which in the cells is accompanied by IR. However, in more complex systems, such as in men and experimental animal models, the link between plasma NEFA delivery to skeletal muscle, mitochondrial impairment and insulin resistance is less strong.…”
Section: Mitochondrial Dysfunction In Insulin Resistancesupporting
confidence: 61%
“…The above hypothesis is supported by the observation that the exposure to saturated fatty acids of isolated mitochondria (Abdul-Ghani et al 2008) or cells (Hirabara et al 2010, Jheng et al 2012, Yang et al 2012, Teodoro et al 2014 clearly elicits mitochondrial dysfunction, which in the cells is accompanied by IR. However, in more complex systems, such as in men and experimental animal models, the link between plasma NEFA delivery to skeletal muscle, mitochondrial impairment and insulin resistance is less strong.…”
Section: Mitochondrial Dysfunction In Insulin Resistancesupporting
confidence: 61%
“…(F) Insulin sensitivity index (ISI; L 4 /mmol 2 *mU 2 ); statistical comparisons were made by Mann-Whitney U test; *p < 0.05; mean ± SEM. See also Figure S4. tolerance has been reported after melatonin therapy (RubioSastre et al, 2014;Teodoro et al, 2014). The use of different species and experimental models may be a reason for these discrepancies.…”
Section: Discussionmentioning
confidence: 93%
“…Secondly, our study is the first to show the arsenite-induced reduction in PGC-1α levels, a transcriptional co-activator which controls mitochondrial biosynthesis [48][49][50]. Previous studies have reported that melatonin improved mitochondrial function by promoting PGC-1α-dependent mitochondrial biogenesis in hepatocytes [51] and skeletal muscle cells [52]. Accordingly, melatonin may maintain mitochondrial mass by increasing PGC-1 levels in arsenite-treated primary cultured cortical neurons.…”
Section: Melatonin Attenuates Arsenite-induced Mitochondrial Lossmentioning
confidence: 85%